Ahasuerus and the Scroll of the Torah: A Literary-Theological Note on Esther 1 - Berger, Yitzhak (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2025)
The book of Esther, particularly at the very beginning, features distinctive language that implies a contrast between the flamboyant and self-indulgent Ahasuerus, on the one hand, and the ideal Israelite king, on the other. The text draws this contrast by way of multiple allusions to kings who, consistent with the law in Deuteronomy, adhere to the teachings found in “the Scroll of the Torah.” This conclusion supports the view that the Jews, under the rule of Ahasuerus, confront a religious challenge in addition to the existential threat initiated by Haman, and that the transformation achieved by Esther and Mordecai bears an implied theological dimension.